Simple, Economical Methods for the Culture of Green Algae for Energy Harvesting from Photosynthesis in a Microfluidic Environment. Issue 12 (12th December 2021) - Kuruvinashetti, Kiran; Rahimi, Soroush; Pakkiriswami, Shanmugasundaram; Packirisamy, Muthukumaran
Abstract: Ongoing technological advancements continually increase the demand for energy. Among various types of energy harvesting systems, biologically based systems have been an area of increasing interest for the past couple of decades. Such systems provide clean, safe power solutions, mainly for low‐ and ultra‐low‐power applications. The microphotosynthetic power cell (μPSC) is one such system that make use of photosynthetic living cells or organisms to generate power. For strong performance, μPSC technology, because of its interdisciplinary nature, requires optimal engineering of both electrochemical cell design and the culture conditions of the photosynthetic microorganisms. We present here a simple, economical culture method for the photosynthetic microorganism Chlamydomonas reinhardtii suitable for the application of this biologically based power system in any geographical location. This article provides a series of protocols for preparing materials and culture medium designed to facilitate the culture of a suitable C. reinhardtii strain even in a non‐biological laboratory. Possible challenges and methods to overcome them are also discussed. Cultured C. reinhardtii perform sufficiently well that they have already been successfully utilized to generate power from a μPSC, generating a peak power of 200 μW from just 2 ml of exponential‐phase algal culture in a μPSC with an active electrode surface area of 4.84 cm 2 . The μPSC thus has potentially broad applications in low‐ and ultra‐low‐power devices and sensors. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Algal growth conditions and algal growth chamber fabrication Basic Protocol 2 : Preparation of Tris‐acetate‐phosphate (TAP) nutrient medium Basic Protocol 3 : Preparation of suspension algal culture from algal strain Basic Protocol 4 : Preparation of stock culture plates (algal strain) from suspension algal culture